Significantly changed intergranular corrosion and exfoliation corrosion behavior of the ultra‐fine grained Al–5 mass% Cu alloy fabricated by ECAP. Issue 11 (18th January 2013) - Song, D.; Ma, A. B.; Jiang, J. H.; Lin, P. H.; Lu, F. M.; Zhang, L. Y.
Abstract Significantly changed intergranular corrosion (IGC) and exfoliation corrosion (EFC) behaviors of the equal‐channel‐angular‐pressed (ECAPed) Al–Cu alloy were discovered through immersion test, electrochemical measurements, and microstructure observation. The ECAPed alloys with ultra‐fine grained (UFG) α(Al) matrix and extremely refined θ‐phase particles displayed obvious decreased IGC sensitivity, but deteriorated susceptibility to EFC. The decreased IGC sensitivity of ECAPed alloys presented decreased IGC propagation depths in immersion test in NaCl + H2O2 solutions and increased polarization resistance in electrochemical impedance spectrum test in MIL‐H‐600 solution. The reason for the decreased IGC sensitivity was the breakage of the net structure of θ phase during ECAP process, which destroys the continuity of IGC propagation channel. The deteriorated susceptibility to EFC of ECAPed alloys in EXCO solution presented gradual evolution from serious IGC attack into obvious lamellar EFC, and finally complete dissolution of surface grains. Meanwhile, the EFC propagation depths were sharply decreased with the increasing ECAP passes. This phenomenon was caused by the aspects ratio evolution of deformed grains and the gradually decreased IGC sensitivity of the ECAPed alloys.